Analisis Finansial Usaha Budidaya Udang Vanamei (Litopenaeus Vannamei) Sistem Intensif di PT. Sumber Agro Sulawesi (SAS) - Rahmi Auliah; Abdullah Abdullah; Budiman Haruna (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2025)
This research aims to determine the total production costs, total revenue and business income, as well as the break-even point, return on investment, revenue to cost ratio, and payback period in the cultivation of vannamei shrimp (litopenaeus vannamei) over a period of 6 months. The research will be conducted from July to December 2024. It employs a quantitative analysis method with interviews and field observations to collect data. The results of this study show that the total costs incurred amount to Rp 2,370,177,864. Meanwhile, the total revenue generated is Rp 2,798,691,706 and the total business income is Rp 428,513,842. Furthermore, the financial analysis includes the Break Event Point (BEP) or break-even point obtained for this business, which is a BEP price of Rp 65,173/kg and a BEP unit of 6,376.09 Kg, the Return On Investment (ROI) for this business is 22%, the Revenue to Cost Ratio (R/C Ratio) for this business is 1.18, and the Payback Period (PP) for this business is 4.46.